(untitled) (World Bulletin of Management and Law, 2024)
In this article, the author divided the historical-legal analysis of the formation of the contractual-legal basis between the Republics of Uzbekistan and Turkey into three stages. The content and essence of the international agreements between the Republics of Uzbekistan and Turkey and their specific features have been systematically studied and scientifically and theoretically substantiated. Uzbekistan’s diplomatic relations with Turkey and the development of international legal cooperation were analyzed using special, logical, political, theological, systematic, and normative interpretation methods.